THE INFLUENCE OF WORK ENVIRONMENT AND WORK STRESS ON EMPLOYEES' INTENTION TO LEAVE AT THE REGIONAL DISASTER MANAGEMENT AGENCY OF BOGOR CITY - Fauzan Fathurahman; Muhamad Aziz Firdaus; Anuraga Kusumah (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to analyze the influence of work environment and work stress on employees' intention to leave at the Regional Disaster Management Agency (BPBD) of Bogor City, and to examine the role of work stress as an intervening variable in the relationship between work environment and intention to leave. The study is motivated by increasing labor mobility in the public sector and the high proportion of contract-based employees (PPPK) at BPBD Bogor City, which has the potential to affect organizational stability. This research employs a quantitative approach using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method through SmartPLS version 4.2.9. Data were collected through a saturated sampling (census) technique by distributing questionnaires using a Likert scale to all 72 employees of BPBD Bogor City. The results of hypothesis testing reveal that work environment has a positive and significant effect on employees' intention to leave, with a path coefficient of 0.429, a t-statistics value of 4.349, and a p-value of 0.000. Work stress also has a positive and significant effect on intention to leave, with a path coefficient of 0.351, a t-statistics value of 4.254, and a p-value of 0.000. Furthermore, work environment has a positive and significant effect on work stress, with a path coefficient of 0.293, a t-statistics value of 2.938, and a p-value of 0.003. Work stress is also proven to significantly mediate the effect of work environment on intention to leave, with an indirect path coefficient of 0.103, a t-statistics value of 2.266, and a p-value of 0.023. These findings indicate a relationship pattern that runs contrary to common theoretical expectations, which can be explained through the Job Demands-Resources (JD-R) Model and the contextual characteristics of BPBD employees. The findings suggest that improving the quality of the work environment at BPBD Bogor City must be accompanied by systematic work stress management strategies in order to effectively reduce employees' intention to leave.